Switzerland : Technical Note-Systemic Risk and Contagion Analysis. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This Technical Note on Systemic Risk and Contagion Analysis on Switzerland summarizes the systemic risk and contagion analysis undertaken for the Swiss financial system as part of the Financial Sector Assessment Program (FSAP) Update. Contagion risks arising from interbank exposures in Switzerland appear to be contained. This analysis shows only moderate effects, consistent with restrictions imposed by the Swiss 'large exposure rules' currently in place, and no material second round effects will materialize within the domestic interbank market. In terms of bank groups, domestic interbank exposure risks appear to be moderate for most banks, but a few small private banks and banks specialized in asset management appear to be somewhat vulnerable. The international contagion analysis suggests that global contagion risks among Global Systemically Important Financial Institutions and the large Swiss financial institutions appear to be currently contained. The systematic risk analysis shows that the relative contribution of domestically oriented banks to systemic risk is increasing. The bank-sovereign contagion analysis suggests that increases in banks capital buffers have contributed positively to limit contagion risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet